Greening Nigeria’s Cities: A Case Study on Renewable Energy in Sustainable Urban Development - Unegbu, Hyginus; Yawas, Danjuma Saleh; Dan-asabe, Bashar; Alabi, Abdulmumin Akoredeley (Universitas Katolik Parahyangan, 2025)
This study examines how renewable energy can be used in sustainable building projects in three major Nigerian cities: Lagos, Abuja, and Port Harcourt. It looks at the potential of solar panels (PV systems), wind energy, and converting biomass waste into energy to reduce both energy use and greenhouse gas emissions. To gather insights, the research involved interviews, site visits, and computer simulations using energy modelling software. The analysis included cost-benefit studies, sensitivity checks, and life cycle assessments to measure both economic and environmental outcomes. Results show that solar PV systems are the most efficient, cutting energy use by 25% to 35% and paying for themselves in 6 to 8 years. Biomass energy showed good potential in industrial areas, while wind energy is less common due to high upfront costs and slower returns. The study highlights key challenges such as high starting costs, limited technical skills, and weak enforcement of energy policies. To overcome these barriers, the paper suggests increasing financial support, strengthening policy implementation, investing in local skills development, and encouraging public-private partnerships to promote the use of renewable energy in Nigerian cities.